Reinterpretation of the Principle of Family, Chapter 33 of the 1945 Constitution of the Republic of Indonesia in the Era of Platform Capitalism within the Framework of the Modern Economy of the 21st Century - KM Ibnu Shina Zaenudin; Rika Nurhayati; Bakar Bakar (Rechtsvinding, 2026)
The modern economy, which relies on Big Data architecture and sophisticated algorithms, presents a disturbing information loop in today's development landscape. This research uses a normative-empirical legal research method (socio-legal research) with a contextual and comparative approach. Philosophically, the principle of kinship in Chapter 33 of the 1945 Constitution of the Republic of Indonesia rejects the liberal anthropological view that views humans solely as rational, selfish, profit-seeking creatures. In relation to the implementation of the contemporary social function of the digital economy, this demands a bold regulatory strategy to counter the concentration of power in the digital oligarchy. The first strategy is to redefine data ownership through the establishment of Data Cooperatives or Data Trusts. By making workers the owners of the platform, profits no longer flow abroad or to a handful of investors but circulate back into the worker community itself, creating a healthy and equitable economic circulation as mandated by Article 33 of the 1945 Constitution of the Republic of Indonesia.